Response of leaf biomass, leaf and soil C:N:P stoichiometry characteristics to different site conditions and forest ages: a case of Pinus tabuliformis plantations in the temperate mountainous area of China - Wang, Yutao; Zhang, Yiming; Wang, Lijiao; Jing, Xin; Yu, Lei; Liu, Ping (Frontiers in Plant Science, 2022)
Ecological stoichiometry is an important index that reflects the element cycle and ecosystem stability. In this study, two sites (sunny and shady slopes) and five forest ages (young stage, half-mature stage, near-mature stage, mature stage, and over-mature stage) in a Pinus tabuliformis plantation were chosen to illustrate the effects of forest ages and site conditions on the biomass and stoichiometric characteristics of leaves and soils in the temperate mountainous area of China. Except for young stage, the biomass, of the leaves of P. tabuliformis on sunny slopes were higher than those on shady slopes in other forest ages, the average carbon content of the leaves in sunny slopes was higher than that in shady slope, while the average total nitrogen contents and average total phosphorus contents of the leaves showed the opposite of this. The biomass of leaves increased on sunny slopes, and increased first and then decreased in shady slopes with increasing forest ages. The contents of soil total carbon (STC) and soil total nitrogen (STN) decreased with increasing soil depth, while the soil total phosphorus (STP) and soil available phosphorus (SAP) contents displayed the opposite. In addition to SAP, the average content of STC, STN, and STP in shady slopes was higher than that in sunny slopes, and the ratio was the opposite. Except for STC: STN on shady slopes, the other ratios showed a downward trend with an increase in soil depth. Excluding the topsoil, the change trend of STC:STP and STN:STP in shady slopes and sunny slopes was consistent with forest ages. The results showed that forest ages and site conditions had significant effects on leaf biomass. The biomass of the leaves is mainly limited by nitrogen. These results have important significance in improving the refinement of local forestry management of Pinus tabuliformis plantations in the temperate mountainous area of China.